Arbeitsgruppe Interoperabilität: Kerndatensatz und Informationssysteme für Integration und Austausch von Daten in der Medizininformatik-Initiative - Ammon, Danny; Kurscheidt, Maximilian; Buckow, Karoline; Kirsten, Toralf; Löbe, Matthias; Meineke, Frank; Prasser, Fabian; Saß, Julian; Sax, Ulrich; Stäubert, Sebastian; Thun, Sylvia; Wettstein, Reto; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
The interoperability Working Group of the Medical Informatics Initiative (MII) is the platform for the coordination of overarching procedures, data structures, and interfaces between the data integration centers (DIC) of the university hospitals and national and international interoperability committees. The goal is the joint content-related and technical design of a distributed infrastructure for the secondary use of healthcare data that can be used via the Research Data Portal for Health. Important general conditions are data privacy and IT security for the use of health data in biomedical research. To this end, suitable methods are used in dedicated task forces to enable procedural, syntactic, and semantic interoperability for data use projects. The MII core dataset was developed as several modules with corresponding information models and implemented using the HL7® FHIR® standard to enable content-related and technical specifications for the interoperable provision of healthcare data through the DIC. International terminologies and consented metadata are used to describe these data in more detail. The overall architecture, including overarching interfaces, implements the methodological and legal requirements for a distributed data use infrastructure, for example, by providing pseudonymized data or by federated analyses. With these results of the Interoperability Working Group, the MII is presenting a future-oriented solution for the exchange and use of healthcare data, the applicability of which goes beyond the purpose of research and can play an essential role in the digital transformation of the healthcare system.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Data integration center; FHIR; Research data infrastructure; Secondary Use; Terminology services